2012
DOI: 10.1055/s-0032-1322545
|View full text |Cite
|
Sign up to set email alerts
|

A 30-Year-Single-Center Experience in Atrial Myxomas: From Presentation to Treatment and Prognosis

Abstract: Symptoms in our cardiac myxoma patients were more pronounced when the myxomas were left-sided, racemous, and over 5 cm in diameter. Even in asymptomatic patients, a high index of suspicion assured timely diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…In addition, a prevalence of female sex was found (female/male ratio=2.6: 1). Our results are consistent with previous case studies involving populations from France, Germany, the United States, Austria, and Korea [ 6 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, a prevalence of female sex was found (female/male ratio=2.6: 1). Our results are consistent with previous case studies involving populations from France, Germany, the United States, Austria, and Korea [ 6 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 93%
“…Tumor size in myxomas as a risk factor of embolism was inconsistent in previous studies [ 7 , 13 , 15 , 23 ]. Our study found that tumor size did not differ significantly between the embolic and non-embolic groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although typically a benign tumour, complications do occur – mainly due to mechanical obstruction caused by the myxoma or embolic phenomena (due to the friable nature of myxomas) (5). Of note, embolization and prolapse of the myxoma through valves are more common in polypoid tumours compared to round/oval myxomas (6).…”
Section: Discussionmentioning
confidence: 99%